Rapidly developed, optimized, and applied wastewater surveillance system for real-time monitoring of low-incidence, high-impact MPOX outbreak - Chandler H. Wong; Zhihao Zhang; Walaa Eid; Julio Plaza-Diaz; Pervez Kabir; Shen Wan; Jian-Jun Jia; Elisabeth Mercier; Ocean Thakali; Lakshmi Pisharody; Nada Hegazy; Sean E. Stephenson; et al. (Journal of Water and Health, 2023)
Recent MPOX viral resurgences have mobilized public health agencies around the world. Recognizing the significant risk of MPOX outbreaks, large-scale human testing, and immunization campaigns have been initiated by local, national, and global public health authorities. Recently, traditional clinical surveillance campaigns for MPOX have been complemented with wastewater surveillance (WWS), building on the effectiveness of existing wastewater programs that were built to monitor SARS-CoV-2 and recently expanded to include influenza and respiratory syncytial virus surveillance in wastewaters. In the present study, we demonstrate and further support the finding that MPOX viral fragments agglomerate in the wastewater solids fraction. Furthermore, this study demonstrates that the current, most commonly used MPOX assays are equally effective at detecting low titers of MPOX viral signal in wastewaters. Finally, MPOX WWS is shown to be more effective at passively tracking outbreaks and/or resurgences of the disease than clinical testing alone in smaller communities with low human clinical case counts of MPOX. HIGHLIGHTS MPOX wastewater surveillance emphasizes solids fraction enrichment.; G2R_G assay with CDC probe offers sensitive MPOX detection.; Longitudinal MPOX wastewater surveillance overall correlates with clinical cases.; Wastewater surveillance provides accurate incidence data in smaller communities.; Rapid MPOX surveillance aids tracking of low-incidence outbreaks.;